СРАВНИТЕЛЬНЫЙ АНАЛИЗ КОНСТРУКТИВНЫХ МОДИФИКАЦИЙ ЭЛЕКТРОГЕНЕРАТОРА МАЛОЙ МОЩНОСТИ С ПОСТОЯННЫМИ МАГНИТАМИ И ЯВНОПОЛЮСНЫМ СТАТОРОМ - Гребеников, В.В. (Інститут електродинаміки НАН України, Київ, 2013)
Comparative calculation results of magnetic fields and electromagnetic torque of electric generators with permanent magnets and salient poles on the stator are shown in this article. Two types of structural modifications of the rotor - with tangential and radial magnetization of permanent magnets are being studied as well. Also optimization calculations based on variations of the outer radius of the rotor, the pole tips thickness of the stator and size of permanent magnets for two structural modifications of electric generators are carried out. It is shown, when there are the same external dimensions, the best one according to the value of braking torque is the electric generator with tangential magnetization of permanent magnets. References 7, figures 5.